Electromagnetic nondestructive evaluation (XVll) - International Workshop on Electromagnetic Nondestructive Evaluation (18th : 2013 : Bratislava, Slovakia); Capova, Klara; Udpa, Lalita, editor; Janousek, Ladislav; Rao, B. P. C., editor (Amsterdam ; Washington, DC : IOS Press, 2014)
Includes bibliographical references and indexes